The Distribution of Using Clean Water Facilities in Poasia District Kendari City - Tosepu, Ramadhan; Nurjannah, Besse; Aprindah, Renni; Kendek Rost Nur Afiat Wahyuni, Esther; Pratiwi, Dian (KnE Social Sciences, 2023)
As an international health organization, World Health Organization (WHO) states that clean water is used by humans to meet their domestic needs, starting from consumption, drinking, and food preparation. This study aimed to describe the use of clean water facilities in Poasia District, Kendari City, in 2022. This study employed quantitative descriptive research, which only describes in general how the distribution of clean water facilities in the working are of Poasia Public Health Center, Poasia District, in 2022. This data was obtained from 5 villages in Poasia District, namely Anduonohu Village, Wundumbatu Village, Rahandouna Village, Anggoeya Village, and Matabubu Village. The population was 9074 household heads. The instruments used were laptops, handphones, books, and pens to record the required data. Based on the results of these secondary data, the majority population in Poasia District used more clean water facilities than well-water from January to October 2022. Moreover, the percentage of clean water for households in Poasia District was higher using well-water (7609) than local water supply utility (1465) of 9074 household heads. The provision of clean water for the community has a very important role in improving environmental or community health, including in terms of reducing the number of people with diseases, especially those related to water, and increasing the standard or level/quality of people’s lives. Keywords: clean water, public health center, Kendari, Sulawesi Tenggara